Roles of Middle Management towards Accountingization in Health Care Organizations - Inoue Shuichi (メルコ管理会計研究, 2021)
The purpose of this paper is to clarify the process of the role of middle management towards “Accountingization” (Power and Laughlin 1992, p.133) in healthcare organizations through an in-depth case study.　 Accountingization is defined as a situation which frontline operations are distorted as a result of accounting control. There are two roles of middle management in Accountingization in a healthcare organization, which are “Absorption”(Laughlin et.al. 1994ab; Broadbent and Laughlin, 1998) and “Two-way windows”(Llewellyn 2001)　 “Absorption” means that middle management absorbs accounting influence indicated by top management; separating accounting and frontline activities. “Two-way windows” means that while middle management translates accounting information indicated by top management to frontline operations, they also work as consolidating opinions from the frontline and communicate with top management to reflect these opinions into strategy and planning, connecting accounting and frontline operations.　 Research question is as follows; how middle management functions as “Absorption” or “Two-way windows” towards Accountingization in frontline operations. This paper conducts interviews and on-site observations in a middle-sized hospital in an ordinance-designated city. Three findings are clarified through in-depth case study. 　 (1) Middle management act as “Absorption” in order to protect frontline operations from accounting pressure by the top management. In this situation, management accounting systems and frontline operations are maintained in loose coupling or decoupling. 　 (2) Middle management switches from “Absorption” to “Two-way windows” triggered by failing financial performances. In this situation, management accounting systems and frontline operations are connected.　 (3) Middle management could switch from “Absorption” to “Two-way windows” if executive office provides a fine grain accounting information including each clinical department’s profit data to frontline staffs.　 This paper contributes to existing literatures in terms of expansion of a concept of Accountingization and adding these process -based knowledge to Accountingizaiton discussion. 本稿の目的は，医療機関の「会計化（Accountingization）」（Power and Laughlin 1992）におけるミドルマネジメントの役割について，in-depthのケース・スタディを採用し，そのプロセスを明らかにすることである。 会計化は，現場が会計コントロールによる影響を受けた結果，現場の活動が本来の姿から歪められてしまうような状態を意味する。会計化に対し，ミドルマネジメントは「吸収役（Absorption）」（Laughlin et. al. 1994ab；Broadbent and Laughlin 1998）と「双方向の窓（Two-way windows）」（Llewellyn 2001）という2つの役割を果たすことが指摘されている。 「吸収役」は，トップマネジメントから現場に対する会計の影響を吸収し，現場が活動に集中できるよう保護する役割である。「双方向の窓」は，ミドルマネジメントがトップマネジメントの示す会計情報を翻訳し，現場に浸透させる一方で，現場の意見を集約し，それをトップマネジメントにフィードバックする役割である。 本稿では，「医療機関のミドルマネジメントは，トップマネジメントからの会計的な圧力に対し，どのように吸収役や双方向の窓の役割を果たしているのか」というリサーチ・クエスチョンを設定し，ある政令指定都市の中規模私立総合病院を対象としたインタビューおよび参与観察を実施した。調査の結果，以下の3点が明らかとなった。 ⑴ミドルマネジメントは，現場への会計的な圧力によって現場の本来の姿が歪められてしまうことを防ぐために，吸収役としての役割を果たす。この場合，管理会計システムと現場の活動はルース・カップリングあるいはディカップリングの状態で維持される。 ⑵業績悪化をトリガーとして，ミドルマネジメントは吸収役を維持できなくなり，双方向の窓に役割が切り替わる。この場合，管理会計システムと現場の活動の連動が図られる。 ⑶各診療科別の損益データをはじめとした粒度の細かいデータをタイムリーに現場に提供することによって，ミドルマネジメントの役割が吸収役から双方向の窓に切り替わる可能性がある。 本稿は，Power and Laughlin（1992）で議論されている会計化の概念を拡張したうえで，上記⑴，⑵，⑶という経験的なデータに基づくプロセスベースの知見を加えたことに貢献がある。